In Vitro Adventitious Shoot Proliferation of Three Basil Species (Ocimum sp. L.) by Addition of Naphthalene Acetic Acid (NAA) and Benzyl Amino Purine (BAP) - Wiendi, Ni Made Armini; Putri, Devina Daratyama (Department of Agronomy and Horticulture, IPB University, 2017)
Basils are mainly used as food flavoring and source of aromatic oil, but the leaves have also been used for herbals and cosmetics. Basil is propagated by seeds but the germination is often low in the field. This study aims to investigate the effect of different concentrations of NAA (Naphthalene Acetic Acid) and BAP (Benzyl Amino Purine) to induce the adventitious shoot proliferation of three species of basil (Ocimumsp. L.) in vitro. The research was conducted at the Tissue Culture Laboratory II of the Department of Agronomy and Horticulture, Bogor Agricultural University (IPB) from November 2016 till October 2017. This research consisted of three separate experiments with one basil species for each experiment, Lemon Basil, “Greek Minette”, and “Thai Siam Queen”. The experiments were organized in a completely randomized block design with two factors: NAA concentrations (0, 0.5, and 1 mg.L-1) and BAP (0, 1, 2, and 3 mg.L-1) using Murashige and Skoog (MS) medium supplied with 25 ml.L-1 coconut water. The three basil species responded differently to NAA and BAP in the media. The optimum concentration of NAA and BAP to induce callus growth in Lemon Basil was 0.5 mg.L-1 and 3 mg.L-1, respectively, with BAP alone showing the best effect on proliferation. In “Greek Minette”, however, the addition of NAA and BAP had no significant effect on the callus growth, proliferation, height, and number of leaf, node and root per explant. Media without growth regulators provide the best results in increasing height, explant proliferation rate, number of nodes and shoots, and percentage of proliferating shoots of “Thai Siam Queen”.Keywords: cytokinin, “Greek Minette”, Lemon Basil, “Thai Siam Queen”, synthetic auxin